The Handbook of Persian Dialects and Dialectology
X, 525 p. 328 illus., 77 illus. in color.
Keywords: This innovative, investigative, and expansive handbook covers a multitude of angles through which the intricacies of Persian and its many dialects and accents can be examined and parsed with the view of understanding better the devices and paths through which language, and cultural cognizance, operate in tandem. As the first book in English to engage Persian dialects and dialectology on a broad and comprehensive scale, it develops an understanding of the paths through which maximization of the expressive power of words exists in Persian under the rubric of cultural conceptualizations. An insightful and all-encompassing resource for analyzing and augmenting knowledge of Persian linguistics, this work presents a thorough and all-encompassing interdisciplinary treatment of Persian. It is a vital resource for socio- and cultural linguists, as well as anthropologists and Iranists. It is also an excellent reference for historians researching Persian civilization, culture, literature and art.